The Republicans’ civil war: Dwight D. Eisenhower and the fight to halt conservatism, 1952–1969 - Cantone, Amy Elizabeth (Kansas State University, 2012)
In the years immediately after World War II, Dwight D. Eisenhower insisted that he did not want to run for office. However, the general, persuaded by the efforts of Citizens for Eisenhower groups, reversed his decision before the 1952 election. The new politician did not take an easy path to the White House, however, as Senator Robert Taft of Ohio, the leading conservative Republican, fought to represent the GOP. Eisenhower aligned with the moderate faction, the party’s traditional source of power, and joined the Republicans during the early stages of a civil war in the party. From the time Eisenhower received the presidential nomination in 1952 until his death in 1969, he committed himself to leading the GOP and establishing moderate, not conservative, Republicanism as the party’s ideology. However, this aspect of Eisenhower’s political career has largely been ignored by historians. The analyses of Eisenhower that focus on his presidency, rather than his military career, concentrate on policy decisions, omitting the president’s role as party leader during a transformative era. This oversight not only skews Eisenhower’s legacy but also renders analyses of the conservative revolution in American politics incomplete. Before conservative Senator Barry Goldwater secured the Republican nomination in 1964, a very important moment that augured —but did not guarantee — the future triumph of the conservative wing, Eisenhower worked to stop his campaign. Had Eisenhower succeeded, the GOP and American politics could have followed a much different trajectory in the twentieth and twenty-first centuries. Utilizing documents from throughout Eisenhower’s political career, this study argues that although Eisenhower failed to halt conservatism, he influenced the course of the GOP. During the 1950s and 1960s, Eisenhower helped revitalize the party, improved the party’s organization, and contributed to conservatism’s delayed ascendancy. Furthermore, Eisenhower merits recognition as a party leader who worked tirelessly on behalf of moderate Republicanism, not just as a man with impressive coattails for Republicans to cling to during elections.
Keywords: Dwight D. Eisenhower; Republican Party; Moderate Republicanism; Conservatism; Richard M. Nixon; American History (0337)